The Relationship Between Soil Fertility and Basal Stem Rot Disease in Oil Palm Plantations - Evan Purnama Ramdan; Arief Hartono; Giyanto Giyanto; Sri Hendrastuti Hidayat; Widodo Widodo (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2023)
In oil palm, Ganoderma boninense causes stem rot disease, which is often difficult to control, and soil fertility status is related to the ecology of G. boninense as a soil-borne pathogen. Therefore, this study aims to evaluate the relationship between soil fertility and stem rot disease as well as appropriate management methods to control the disease. This was carried out at the Nusantara Plantation Company's 7, Unit Kiwah Rejosari-Pematang from June 2021 to January 2022. The determination of observation blocks was carried out selectively using three blocks of land attacked by Ganoderma boninense with the same criteria for the year of planting and the same soil type. Each block consists of five plots. Each plot consisted of five sub-plots, consisting of 3 oil palms for disease severity assessment and soil sampling. The soil for each subplot was composed of 15 samples, which were analyzed for physical and chemical properties of the soil. Determination of fertility status based on the soil research manual published by the Indonesian Bogor Soil Research Center with parameters from the analysis results. The limiting factor for fertility is the cation exchange capacity of the soil, which ranges from 10.07 meq/100 g to 17.68 meq/100  g, and the C-organic content, which ranges from 0.40 to 1.15%. According to chi-square analysis, this fertility-limiting factor is related to disease severity. Therefore, management needs to be done by adding organic matter to the soil, practicing organic or inorganic fertilization, and following the principles of cultivating healthy oil palm plants.